Achieving behavioral health equity for children, families, and communities : proceedings of a workshop - Tracey, Sarah M. (National Academies Press, 2019)
In November 2017, the The Forum on Promoting Children's Cognitive, Affective, and Behavioral Health, in collaboration with the Roundtable on the Promotion of Health Equity, convened a workshop on promoting children's behavioral health equity. The workshop used a socio-ecological developmental model to explore health equity of children and families, including those with complex needs and chronic conditions. Particular attention was paid to challenges experienced by children and families in both rural and urban contexts, to include but not limited to poverty, individual and institutional racism, low-resourced communities, and hindered access to educational and health care services. Workshop participants also engaged in solution-oriented discussions of initiatives, policies, and programs that aim to improve social determinants of health, opportunities for behavioral health promotion, and access to quality services that address the behavioral health of all children and families. This publication summarizes the presentations and discussion of the event.